Ruminal Acidosis Part II: Diagnosis, Prevention and Treatment - Voulgarakis, N; Athanasiou, LV; Psalla, D; Gougoulis, D; Papatsiros, V; Christodoulopoulos, G (Journal of the Hellenic Veterinary Medical Society, 2024)
Ruminal acidosis is presented as the most significant nutritional disorder of ruminants with severe impact on animal health, welfare and considerable economics losses in ovine and bovine herds. The disease is presented in two forms Acute Ruminal Acidosis (ARA) and Sub-Acute Ruminal Acidosis (SARA). This second part of the Ruminal Acidosis review focuses on the diagnosis, prevention, and treatment. The diagnosis of SARA presents several difficulties due to the non- clinically patent symptoms. Prevention and treatment are based on the amelioration of nutrition including the use of dietary supplements, and antimicrobial administration as well as the improvement of management practices.